Konsep Legalitas Perkawinan dalam Kompilasi Hukum Islam : Kajian Hukum dan Sosial - Siska Ayu Anggraini; Rachmat Panca Putera (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study discusses the concept of marriage legality in the Compilation of Islamic Law (KHI) as a legal guide for marriage in Indonesia. Marriage legality plays a crucial role in maintaining social order and legal validity, as well as ensuring the rights and obligations of the husband, wife, and children born from the marriage. This research aims to identify the concept of marriage legality in KHI and analyze the impact of legal and social aspects on its implementation. The research method used is a qualitative approach with normative and sociological analysis, as well as a literature study of KHI documents, relevant laws, and scholarly references. The findings of the study show that although KHI provides a clear legal basis for marriage legality, practices such as unregistered marriage (nikah siri) and contract marriages are still prevalent in society, leading to social disorder. The implication of this study is the importance of a deeper understanding of marriage legality in KHI to raise public legal awareness and maintain social order.